OVERVIEW OF WOMEN'S LEGAL ANALYSIS AS A CRIMINAL ACT OF DRUG CIRCULATION IN MEDAN CITY - Sonya Airini Batubara (Faculty of Law, Universitas Pekalongan, 2024)
Medan as the third largest city in Indonesia, which is where the spread of narcotics illicit trafficking cases often occurs, making the city of Medan the largest recipient of narcotics illicit trafficking cases in Indonesia, this causes women to be involved in narcotics illicit trafficking crimes which have violated the noma and decency from women. The law enforcement officers, in this case the National Narcotics Agency of North Sumatra Province, are active in carrying out their duties and authorities in eradicating and preventing women in North Sumatra, especially in the city of Medan. The results of this study use the nature of quantitative research and normative juridical methods and are strengthened from empirical juridical, which examines scientific material, legislation, and conducting research or mini-research at the Medan Women's Class II A Prison and the BNNP SUMUT. The results showed that the number of cases of illicit narcotics trafficking that arose among women in the city of Medan was caused by economic factors and local environmental factors. Of the many cases of illicit drug trafficking among women, the BNNP SUMUT has implemented several policies through repressive and preventive efforts and carried out the P4GN program. Until now cases of illicit drug trafficking carried out by women are still common, this is due to the lack of awareness of the role of the community in the city of Medan. Of the many cases of illicit drug trafficking among women, the BNNP SUMUT has implemented several policies through repressive and preventive efforts and carried out the P4GN program. Until now cases of illicit narcotics trafficking carried out by women are still common, this is due to the lack of awareness of the role of the community in the city of Medan. Of the many cases of illicit drug trafficking among women, the BNNP SUMUT has implemented several policies through repressive and preventive efforts and carried out the P4GN program. Until now cases of illicit narcotics trafficking carried out by women are still common, this is due to the lack of awareness of the role of the community in the city of Medan.